A Multi-Level Multi-Objective Integer Quadratic Programming Problem Under Pentagonal Neutrosophic Environment - Bekhit, N. M.; Emam, O. E.; Elhamid, Laila Abd (Fuzzy information and engineering, 2023)
The aim of this paper is to propose an algorithm to solve and enhance a multi-level multi-objective integer quadratic programming problem (MLMOIQPP) under a single-valued Pentagonal Neutrosophic environment applied to the objective functions. The suggested solution takes advantage of multi-objective optimization in addition to the fuzzy approach as well as the branch and bound technique, which is implemented at each decision level to develop a generalized maximization-minimization model for obtaining the integer satisfactory solution after applying the score and accuracy function in the first phase of the solution methodology to single-valued Pentagonal Neutrosophic parameters to be converted into an equal crisp form. An illustrative example is demonstrated to validate the proposed solution algorithm.